La chirurgie dans l'Egypte gréco-romaine d'après les papyrus littéraires grecs - Marganne, Marie-Hélène. (Studies in Ancient Medicine, 1998)
This volume provides new information on a brilliant but not well known period of the history of surgery. It uses as its point of departure a remarkable but insufficiently known documentation: Greek literary papyri (from I B.C. to A.D. VII), which often are unique witnesses to lost medical works, bearing testimony to original theories, practices and vocabulary. The first part of the book provides an introduction to ancient surgery, to Greco-Roman Egypt and to the Greek medical papyri. The second part presents the critical edition with French translation and commentaries of seven surgical papyri and a chapter on other medical papyri with some information about surgery.